Bounded variation solutions to Sturm-Liouville problems - Jacek Gulgowski (Electronic Journal of Differential Equations, 2018)
In this article we consider singular Sturm-Liouville problems whose right-hand side is a function of bounded Jordan variation. We present necessary and sufficient conditions for all solutions to be of bounded Jordan variation.